The Genetic Component of the Forced Diving Bradycardia Response in Mammals - Fahlman, Andreas; Bostrom, Brian L.; Dillon, Kiran H.; Jones, David R. (Frontiers in Physiology, 2011)
We contrasted the forced diving bradycardia between two genetically similar (inbred) rat strains (Fischer and Buffalo), compared to that of outbred rats (Wistar). The animals were habituated to forced diving for 4 weeks. Each animal was then tested during one 40-sec dive on each of 3 days. The heart rate (fH) was measured before, during, and after each dive. Fischer and Buffalo exhibited marked difference in dive bradycardia (Fischer: 120.9 ± 14.0 beats • min-1 vs. Buffalo: 92.8 ± 12.8 beats • min-1, P < 0.05). Outbred rats showed an intermediate response (103.0 ± 30.9 beats • min-1) but their between-animal variability in mean dive fH and pre-diving resting fH were higher than the inbred strains (P < 0.05), which showed no difference (P > 0.05). The decreased variability in fH in inbred rats as compared with the outbred group indicates that reduced genetic variability minimizes variability of the diving bradycardia between individuals. Heritability within strains was assessed by the repeatability (R) index and was 0.93 ± 0.05 for the outbred, 0.84 ± 0.16 for Buffalo, and 0.80 ± 0.12 for Fischer rats for fH during diving. Our results suggest that a portion of the mammalian diving bradycardia may be a heritable trait.